Context-aware systems and applications, and nature of computation and communication : 7th EAI International Conference, ICCASA 2018, and 4th EAI International Conference, ICTCC 2018, Viet Tri City, Vietnam, November 22-23, 2018, Proceedings /: 7th EAI International Conference, ICCASA 2018, and 4th EAI International Conference, ICTCC 2018, Viet Tri City, Vietnam, November 22-23, 2018, Proceedings. (2019) - Unknown
No abstract available